Paradigmatic basis of economic life as a factor of constituting of civilizational identity of the East Slavic world - Romanov, Oleg A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with a scope of problems connected with the intrinsic logic of organization and development of the economic sphere of the East Slavic civilization. The article is aimed at the explication of sociocultural matrices of economic management in the East Slavic region as well as at the consideration of the mechanisms to bring it to post crisis step of development. The author specifies the notion «economy» and «chrematistics» as applied to ways and types of civilizational dynamics. The article defines sociocultural presuppositions of formation of economic system of the East Slavic and the Western civilizations. The author considers the following presuppositions for genesis of the East Slavic economy: the idea of a man as a conciliar person; the idea of a people as a transpersonal unity which possesses its own historical destiny and collective consciousness; the idea of society as an extended family; the idea of spiritual values as ontologically based reality. It is showed that above mentioned principles in economic sphere gained their interpretation in form of ethics of service as a base for economic life. Economic practices in the East Slavic culture get legitimation not from value of success but from the idea of public good in its wide sense. The article defines sociocultural status of money by means of reconstruction of corresponding myth of the East Slavic culture. The author draws a conclusion that sociocultural base for economic life is a society-family paradigm that presupposes the priority of social over individual interests, material backing of all members of society and slow dynamics of development. Strong points of such type of economic organization are stability and non-crisis development whereas a sufficient drawback lays in low economic effectiveness. Regulating mechanism of the economic life of the East Slavs lays in ethic of duty and service that allows including ethically not irreproachably business activity in civilizational system thus.